2014
DOI: 10.1186/1297-9686-46-46
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing animals for dense genotyping in order to impute missing genotypes of sparsely genotyped animals

Abstract: BackgroundGenotyping accounts for a substantial part of the cost of genomic selection (GS). Using both dense and sparse SNP chips, together with imputation of missing genotypes, can reduce these costs. The aim of this study was to identify the set of candidates that are most important for dense genotyping, when they are used to impute the genotypes of sparsely genotyped animals. In a real pig pedigree, the 2500 most recently born pigs of the last generation, i.e. the target animals, were used for sparse genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Similar results have been previously reported [ 18 , 44 ]. However, Yu et al [ 45 ] found that animals with the closest average relationship or contribution to the target population gave the lowest accuracy imputation, in some cases worse than random selection.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been previously reported [ 18 , 44 ]. However, Yu et al [ 45 ] found that animals with the closest average relationship or contribution to the target population gave the lowest accuracy imputation, in some cases worse than random selection.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not test the marker array genotyping strategy, hybrid peeling performed well with marker array data that were generated following genotyping practices such as those of current breeding programs with genomic selection. Our method does not replace routine marker array genotyping and there exists a body of work on this topic [20,[43][44][45] that can provide marker array genotyping guidelines.…”
Section: Impact Of the Marker Array Genotyping Strategymentioning
confidence: 99%
“…Other pedigree-based methods proposed by Druet et al [7] maximise either the genetic relationship between the sequenced individuals and the rest of the population or, on the contrary, the number of independent genomes captured. The methods based on genomic information typically use haplotype libraries derived from phased marker array genotypes [7,[15][16][17][18][19] or the genomic relationship matrix [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Strategies suggested by Druet et al (2014) and Yu et al (2014) could be used to select individuals to be genotyped on HD-777K with the aim of maximizing imputation accuracy. The result obtained in Nelore and in Gyr in the current study suggests that this conclusion could be valid for other Bos indicus breeds.…”
Section: Imputation Accuracy With Different Snp Chipsmentioning
confidence: 99%